Machine Retrograde Perfusion of Deceased Donor Kidneys: A Prospective Study - Zeng, Jun; Jia, ZiHao; Lin, Tao; Song, TuRun (Frontiers in Medicine, 2021)
Abstract Objective: To maximize the utilization of potential kidneys, improving perfusion and preservation technique is necessary. Methods: We investigated the safety and efficacy of retrograde machine perfusion of kidneys from deceased donor. Thirty kidneys were included and all grafts were preserved in the Kidney Transporter machines. Fifteen kidneys received retrograde perfusion (RP) were selected as the RP group, and their counterparts received standard antegrade perfusion (AP) as control group. Results: All recipients were followed up for six months. Renal resistance in RP group remained stable during the perfusion. There was no primary non-function. No difference in the incidence of delayed graft function was found in both groups (3 in RP vs 2 in AP, p = 0.62). The RP group had lower serum creatinine (RP vs. AP, 102.20 vs. 138.67, p=0.05), blood urea nitrogen (RP vs. AP, 6.44 vs. 8.71, p=0.05) than that in AP group at six months. Both groups had comparable estimated glomerular filtration rate, cystatin c within six months. Conclusions: This novel technique may be an effective and safe alternative for kidney preservation.